THE RELATIONSHIP OF KNOWLEDGE AND MOTHER'S ATTITUDES IN CARRYING OUT BABY SPA FOR BABIES AGED 6-12 MONTHS AT PMB SITI HAJAR MEDAN 2025 - Intan Sari; Kristina Natalia br Naibaho; Ledyta Roulina Sihombing; Martha Samosir; Debi Novita Siregar (PT. Radja Intercontinental Publishing, 2025)
Background:Baby SPA is a form of stimulation that supports infant growth and development. However, many mothers lack sufficient understanding of its benefits and procedures. Educational initiatives are necessary to enhance maternal understanding and promote a constructive attitude. Objective: To explore the relationship between mothers' level of knowledge and their attitudes in conducting Baby SPA for infants aged 6–12 months at PMB Siti Hajar Medan in 2025. Methods: The study adopted a quantitative method with a cross-sectional design. A total of 30 mothers participated, selected through total sampling. Data were gathered using questionnaires and examined through the Chi-Square test with a 0.05 level of significance. Results: The results indicated that 56.7% of the respondents had a strong understanding and demonstrated supportive attitudes toward Baby SPA. A statistically significant and moderately strong positive relationship was identified between knowledge and attitude (p = 0.005; r = 0.531). Conclusion: Mothers with better knowledge tend to show more favorable attitudes toward Baby SPA. Continuous health education is essential to ensure proper and safe implementation of Baby SPA practices.